Information systems development Asian experiences - Song, William Wei; Xu, Shenghua; Wan, Changxuan; Zhong, Yuansheng; Wojtkowski, Wita; Wojtkowski, Gregory; Linger, Henry (Springer, 2011)
Information Systems Development: Asian Experiences, is the collected proceedings of the 18th International Conference on Information Systems Development: Asian Experiences 2009 Conference, held in Nanchang, China. It follows in the tradition of previous conferences in the series in exploring the connections between industry, research and education. These proceedings represent ongoing reflections within the academic community on established information systems topics and emerging concepts, approaches and ideas. It is hoped that the papers herein contribute towards disseminating research and improving practice. The conference tracks highlighted at the Eighteenth International Conference on Information Systems Development (ISD 2009) were: Enterprise Systems : A Challenge for Future Research and Improved Practice Business Systems Analysis IS/IT project management Data and Information Systems Model Human-Computer Interaction in ISD Information Systems for Service Marketing Development of Information Systems for Creativity and Innovation Model-Driven Engineering in ISD Legal and Administrative Aspects of Information Systems Development Information Systems Engineering and Management Agile and High-Speed Systems Development.